Interprofessional Collaboration Implementation Strategy At Bina Kasih Hospital Medan - Marshal Duva Siahaan; Chrismis Novalinda Ginting; Sri Wahyuni Nasution (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
In the services carried out in the hospital, there are various health professional experts involved. Where to run a hospital program that aims at patient safety, a collaboration between health professionals is needed. IPC science is one of the ways used to strive for the improvement of service quality in hospitals. The IPC has several implementation strategies that must be fulfilled in the implementation of the IPC. The purpose is to know the concept and strategy of IPC implementation and obstacles in improving patient safety at Bina Kasih Medan Hospital. The research was conducted at Bina Kasih Hospital, Medan, from July 2022 to August 2022. The methods used are data collection techniques after obtaining ethical permission, conducting in-depth interviews and writing transcripts of interview results and processing data by conducting observations, analyses, relevant independent studies that focus on the implementation of IPC at Bina Kasih Hospital Medan in improving patient safety. Results Based on the search results obtained 4 themes that are an overview of the IPC Implementation Strategy at Bina Kasih Hospital Medan, namely: (1) The concept of Interprofessional collaboration, (2) Practice in implementation at the Hospital, (3) IPC Strategy that occurred at Bina Kasih Hospital, (4) IPC Obstacles that occurred at Bina Kasih Hospital. Conclusion The implementation of the IPC Strategy implemented by Bina Kasih Hospital Medan according to participants has carried out the service well. Keywords: Health Workers, Interprofessional Collaboration, IPC